Effects of running exercise combined with blood flow restriction on strength and sprint performance - Chen, Y. T.; Hsieh, Y. Y.; Ho, J. Y.; Lin, J. C. (The Journal of Strength and Conditioning Research, 2021)
We investigated muscle strength and sprint performance after combining running exercise (RE) with blood flow restriction (BFR). Twelve male sprinters received 2 experimental warm-ups: (a) RE (50% heart rate reserve, 2 minutes × 5 sets, 1-minute rest interval) with BFR (occlusion pressure: 1.3 × resting systolic blood pressure) warm-up, namely RE-BFR; and (b) RE without BFR warm-up, namely RE. Isokinetic strength or 60-m sprint performance was assessed after a 5-minute recovery from each experimental warm-up. All subjects completed 4 exercise trials in a counterbalanced order: (a) RE-BFR-strength; (b) RE-strength; (c) RE-BFR-sprint; and (d) RE-sprint. Muscle activation (during RE), blood lactate (BLa) (pre- and post-REs), heart rate (HR), and rating of perceived exertion (RPE) (pre- and post-REs and at a 5-minute recovery) were determined during each experimental warm-up. The isokinetic knee flexor strength and the hamstring-quadriceps (H:Q) ratio observed for the RE-BFR warm-up were significantly higher than those observed for the RE warm-up (p < 0.05). However, no differences (p > 0.05) in the isokinetic knee extensor strength and 60-m sprint performance were observed between the 2 warm-ups. Running exercise-BFR warm-up induced a higher level of vastus lateralis and biceps femoris muscle activation than did RE warm-up (p < 0.05). Furthermore, RE-BFR warm-up induced higher HR, RPE, and BLa values than did RE warm-up after RE and at a 5-minute recovery (p < 0.05). These results suggest that RE-BFR warm-up may augment physiological responses and improve the H:Q ratio and isokinetic knee flexor strength. Thus, RE-BFR warm-up may be considered a practical warm-up strategy for promoting muscle strength and reducing the risk of hamstring injury in male sprinters.